Evaluation of Osteoporosis and Osteoporotic Fracture Risk in Men: A Retrospective Study - Uğur Ertem; Fatma Jale İrdesel (Türk Osteoporoz Dergisi, 2022)

(untitled)
Objective:Osteoporotic fractures can cause important consequences in terms of public health in men and women. In this study, It is aimed to determine the frequency of osteoporosis (OP) and osteoporotic fractures in men and the risk factors that may cause osteoporotic fractures.Materials and Methods:Men over the age of 65 years who were admitted to physical medicine and rehabilitation outpatient clinic with musculoskeletal system pain between 15 March 2021 and 15 September 2021 was included in the study retrospectively. A total of 90 patients were included in this study. Data regarding 25-hydroxyvitamin D3 [25-(OH)D3] levels, body mass index (BMI), age, bone mineral density (BMD) T-scores, smoking and alcohol using status were recorded.Results:The median age of the participants was 71 (66-89) years. Osteoporotic fractures were found in 14 patients (15.5%). Osteoporotic fractures were more common in the vertebral region (71.4%). The patients were divided into the following two groups: group 1 (with osteoporotic fracture) and group 2 (without osteoporotic fracture). Regression analysis revealed that age, and BMI associated with osteoporotic fractures (p<0.05). In contrast, no correlation was found between osteoporotic fracture formation and 25-(OH)D3 levels, BMD T-scores, smoking, and use of alcohol (p>0.05).Conclusion:OP and osteoporotic fracture formation is a common public health problem in men and women. Because of the negative effects of osteoporotic fractures on society and individuals, it is important to know the risk factors and take precautions against them.